2021
DOI: 10.3390/ph14080734
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Enhance the Suppressive Activity of Extracellular Vesicles in Mouse Delayed-Type Hypersensitivity

Abstract: Previously, we showed that mouse delayed-type hypersensitivity (DTH) can be antigen-specifically downregulated by suppressor T cell-derived miRNA-150 carried by extracellular vesicles (EVs) that target antigen-presenting macrophages. However, the exact mechanism of the suppressive action of miRNA-150-targeted macrophages on effector T cells remained unclear, and our current studies aimed to investigate it. By employing the DTH mouse model, we showed that effector T cells were inhibited by macrophage-released E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
(125 reference statements)
2
5
0
Order By: Relevance
“…On the other hand, almost 20 years ago it was observed that cross-linking of major histocompatibility complex (MHC) class II-expressing EVs with latex beads greatly augments their biological effectiveness ( Vincent-Schneider et al, 2002 ). Similar enhancement was recently demonstrated by us after aggregating MHC class II-expressing EVs with antigen-specific antibodies ( Nazimek et al, 2021 ). These findings imply that EV’s aggregation may increase not only their half-life in circulation, as mentioned above, but also the amount of vesicles targeting desired cell population ( Figures 1 , 2 ).…”
Section: Antigen-specific Antibodies and Light Chains In The Fight To Enhance Extracellular Vesicles Therapeutic Efficacysupporting
confidence: 87%
See 3 more Smart Citations
“…On the other hand, almost 20 years ago it was observed that cross-linking of major histocompatibility complex (MHC) class II-expressing EVs with latex beads greatly augments their biological effectiveness ( Vincent-Schneider et al, 2002 ). Similar enhancement was recently demonstrated by us after aggregating MHC class II-expressing EVs with antigen-specific antibodies ( Nazimek et al, 2021 ). These findings imply that EV’s aggregation may increase not only their half-life in circulation, as mentioned above, but also the amount of vesicles targeting desired cell population ( Figures 1 , 2 ).…”
Section: Antigen-specific Antibodies and Light Chains In The Fight To Enhance Extracellular Vesicles Therapeutic Efficacysupporting
confidence: 87%
“…Moreover, it can be hypothesized that EV’s aggregation together with directing them towards desired target tissue or cell population will greatly enhance their therapeutic efficacy. As discussed below, our results showed that this could be achieved by incubating EVs with antigen-specific antibodies ( Nazimek et al, 2021 ) ( Figure 1 ).…”
Section: Challenges In Therapeutic Application Of Extracellular Vesiclesmentioning
confidence: 62%
See 2 more Smart Citations
“…Remarkably, intragastric administration of miRNA-150-transmitting EVs to mice with elicited cutaneous symptoms of delayed-type hypersensitivity to food allergens, i.e., ovalbumin and casein, significantly ameliorated the course of the contact allergic reaction [ 108 , 109 ]. Based on our other research findings [ 110 ], we suspect that miRNA-carrying EVs could be endocytosed by macrophages in the digestive tract, which would stimulate these cells to release secondary EVs inducing a tolerogenic effect at distant tissues. Altogether, our findings provide research evidence for the possible application of immune regulatory EVs for oral treatment of various diseases, including allergies and autoimmunity diseases [ 111 ].…”
Section: Mammalian Cell-derived Evs—a New Perspectivementioning
confidence: 96%